The ocular pathological findings in professional baseball players - Kirschen, D.; Laby, D. (Journal of Sports and Performance Vision, 2019)
This article highlights the eye findings uncovered among 800 professionals, with no visual complaints. Methods: During their yearly sports vision screenings between 2004 and 2011 these retinal and anterior segment pathologies were detected and documented using a Kowa-Optimed (Hawthorne, CA) non-mydriatic fundus camera. Results: Twelve athletes (1.5%) were found to have ocular pathology in the posterior pole or anterior portion of the eye. The findings were categorized into five groups, nevi, hemorrhages, retinal scars and abnormalities, optic nerve changes, and vascular changes. Conclusion: This work illustrates the importance of eye health screenings as an integral part of a comprehensive sports vision evaluation.